Low Socio Economic Status Risk Improving Attention Deficit and Hiperactivity Disorder in Preschoolers - Setianingsih Setianingsih; Rachmawati Novi; Juniarsih Juniarsih (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Socioeconomic status of person has an important role to child development. Social economy can affect physical health, mental wellbeing and cognitive development. One of the growing disorders of attention disorder and hyperactivity disorder was characterized by hyperactive, impulsive and lack of attention. The purpose of this study to determine the relationship of socioeconomic status of parents at risk of attention deficit and hyperactivity disorder (ADHD) to preschoolers in Klaten District. This study uses categorical comparative design with cross sectional approach. Respondents of this study were 84, that divided into two places, there were ABA TK Lor Sabrang Trucuk and TKIT Mutiara Hati so that every kindergarten 42 respondents obtained by purposive sampling. Data was collection by filling the instrument. Bivariate analysis using test Chi Square. The results showed the average age of respondents were 5.25 years. The sex of the respondents is mostly male as many as 47 children or 56.0%. Test results Chi square show there is a relationship of socio-economic status of parents with ADHD (p = 0.036) and there is a different between low socioeconomic status and high that lower socioeconomic status is a risk of ADHD (25,6%) compared with high socioeconomic status (6,7%). There is a negative relationship between socioeconomic status and the risk of attention deficit and hyperactivity disorder in pre-school age children.